Monitoring and evaluation design of Malawi's Right Foods at the Right Time nutrition program. (April 2019) - Ruel-Bergeron, Julie C.; Hurley, Kristen M.; Kang, Yunhee; Aburto, Nancy; Farhikhtah, Arghanoon; Dinucci, Alessandro; Molinas, Luca; Lee Shu Fune, Wu; Mitra, Maithilee; Phuka, John; Klemm, Rolf; West, Keith; et al.
Abstract: Child stunting is a public health problem in Malawi. In 2014, the Government of Malawi launched the Right Foods at the Right Time (RFRT) program in Ntchisi district delivering nutrition social and behavior change communication, a small-quantity lipid-based nutrient supplement to children 6–23 months, and nutrition sensitive activities. Monitoring and evaluation (M&E) systems are key aspects of successful program implementation. We describe these and the methodology for an impact evaluation that was conducted for this program. Two monitoring systems using traditional and electronic platforms were established to register and track program delivery and processes including number of eligible beneficiaries, worker performance, program participation, and to monitor input, output, and outcome indicators. The impact evaluation used comparative cross-sectional and longitudinal designs to assess impact on anthropometric and infant and young child feeding outcomes. Three cross-sectional surveys (base-, mid-, and end-line) and two longitudinal cohorts of children followed in 6-month intervals from 6 to 24 months of age, were conducted in sampled households in the program and a neighboring comparison district. Additional M&E included qualitative studies, a process evaluation, and a cost-effectiveness study. The current paper describes lessons from this program's M&E, and demonstrates how multiple implementation research activities can inform course-correction and program scale-up.